Ein Beamter der Liechtensteiner Herrschaftsgüter der zweiten Hälfte des 18. Jahrhunderts (Am Beispiel der Herrschaft Lanškroun aus dem Inspektorat Moravská Třebová) - Macková, Marie (Theatrum historiae, 2012)
The officer classes of the Liechtenstein's dominions of the second half of the 18th century were classified into several mutually permeable types. The administrator of each dominion exercised relatively large competences; in spite of that, he or she was still far from being the ruler. The period in question witnessed the core of the officer's work shift from power-based administration towards the use of predominantly economic instruments. The state’s interventions with the system grew more numerous as it defended its own interests.